Improved first-pass effect in acute stroke thrombectomy using Solitaire-X compared to Solitaire-FR - Biederko, Ron; Honig, Asaf; Shabad, Ksenia; Zlotnik, Yair; Ben-Arie, Gal; Alguayn, Farouq; Shelef, Ilan; Horev, Anat (Frontiers in Neurology, 2023)
Background In acute ischemic stroke (AIS), successful endovascular thrombectomy (EVT) of large vessel occlusion (LVO) necessitates the most suited device. Solitaire-X has longer and larger diameter pusher wires than Solitaire-FR. As the role of a larger pusher-wire diameter is uncertain, we aim to compare procedural, clinical, and radiological outcomes for AIS patients undergoing EVT using either type of Solitaire device. Procedures were performed using the Solumbra technique, which combines a large-bore aspiration catheter with a stentriever. The primary outcome was to compare rates of successful first-pass recanalization (defined as TICI 2b/3 score). The secondary objectives were procedural (rates of successful recanalization), clinical (post-procedural NIHSS and days of hospitalization), and radiological (post-procedural ASPECT score and hemorrhagic transformation) outcome measures. Design Consecutive AIS patients undergoing EVT for LVO were recruited into a prospective multicenter database at our academic center. We have used Solitaire-FR until October 2020 and Solitaire-X ever since. We retrospectively analyzed our prospective consecutive registry. Included in our analysis are patients undergoing EVT using Solitaire only; patients with tandem lesions or underlying stenosis requiring emergent stenting during the procedure were excluded. The cohort of patients treated with Solitaire-X was compared with a cohort consisting of the most recent consecutive cases undergoing EVT with the Solitaire-FR. Results A total of 182 (71.9 ± 14, 61% male patients) AIS patients were included in the analysis with both groups (n = 91 each) sharing similar demographic characteristics, premorbid conditions, and stroke characteristics (time from symptom-onset, NIHSS, ASPECTS, occlusion site, and rates of intravenous-tPA treatment). The Solitaire-X group had a higher rate of first-pass recanalization (65.9% vs. 50.5%, p = 0.049). On 24-h post-procedural head-CT, the Solitaire-X group had higher ASPECT scores (6.51 ± 2.9 vs. 5.49 ± 3.4, p = 0.042) and lower post-procedural average bleeding volumes (0.67 ± 2.1 vs. 1.20 ± 3.4 mL, p = 0.041). The Solitaire-X group had shorter duration of hospitalization (16.6 ± 13.1 days vs. 25.1 ± 23.2, p = 0.033). On multivariate analysis, using Solitaire-X was the sole independent predictor of first-pass recanalization (OR 2.17, 95% CI 1.12–4.26, p = 0.023). Conclusion In our study, the use of the Stentriever-X with a larger pusher-wire diameter was associated with a higher likelihood of first-pass effect and improved procedural, clinical, and radiological outcomes in AIS patients.